PENGUATAN DIGITALISASI DAN REBRANDING TERHADAP PELAKU UMKM DI DESA CANDIREJO KABUPATEN MAGETAN - Setyansah, Reza Kusuma; Luthfi Azis, Muh Nur (Fakultas Ekonomi dan Bisnis Islam Institut Pesantren Sunan Drajat Lamongan, 2025)
The Thematic Community Service Program (KKN-T) conducted by Universitas PGRI Madiun in Candirejo Village, Magetan Regency, was strategically focused on community empowerment through a series of integrated initiatives. Core programs included the digitalization of administrative management for community health posts (posyandu), nutrition workshops for mothers, mentoring in digital marketing and product rebranding for MSMEs, the development of Community Reading Gardens (Taman Baca Masyarakat), training in Smart Digital Finance, as well as the establishment of Sustainable Food Houses and Organic Gardens. A flagship initiative centered on strengthening digital transformation among MSMEs, aiming to enhance digital literacy, expand market access, and improve the competitiveness of local products. Field observations identified several key challenges, including low digital literacy, overreliance on manual record-keeping, and limited understanding of digital platforms. These issues were attributed to insufficient training programs, inadequate technological infrastructure, and resistance to change. Structured interventions—comprising targeted training, technology provision, and intensive mentoring—proved effective in addressing these barriers. The program contributed significantly to administrative efficiency, improved the quality of community health services, and optimized MSME marketing strategies through digital platforms and competitive pricing. The findings underscore that digital transformation serves as a critical driver in achieving sustainable competitive advantage for local MSMEs amid the digital disruption era.